Evaluasi Program Magang Mahasiswa: Review Literatur Tentang Kesenjangan Antara Tujuan Kampus, Implementasi Industri, Dan Kompetensi Kerja - Muhammad Harizal; Sufian Hamim; Raden Imam Al Hafis (Journal of Innovative and Creativity (Joecy), 2026)
Student internship programs are often positioned as a strategic bridge between higher education and the world of work. However, the program does not always produce measurable work competencies because university goals, industry implementation, and student learning outcomes are not fully connected in one evaluative design. This article aims to analyze the gap in student internship programs through a literature review focusing on university objectives, industry practices, and work competencies. The study uses an integrative literature review method by examining 20 open access scientific articles published within the last seven years. The analysis is conducted through source identification, thematic classification, comparison of findings, and synthesis of recurring gaps. The findings show that internship programs tend to be strong as academic requirements, but weaker as competency development programs. Universities often formulate internship objectives in broad terms, while industries implement internships according to operational needs. As a result, students may gain workplace exposure without necessarily achieving relevant professional competencies. The review also indicates that internship evaluation is still frequently administrative, focusing on attendance, final reports, and supervisor scores rather than competency achievement. This article concludes that internship programs need stronger alignment among learning outcomes, workplace tasks, joint supervision, and competency based evaluation.